Formation and stability of string phase in polyamide 6/polystyrene blends in confined flow: Effects of nanoparticles and blend ratio. Issue 2 (2nd October 2015) - Kong, Miqiu; Huang, Yajiang; Lv, Yadong; Yang, Qi; Li, Guangxian
Abstract : Influences of silica nanoparticles on the microstructural evolution of polyamide 6 (PA6)/polystyrene (PS) blends with varying blend ratios were investigated in confined shear flow. Hydrophilic silica nanoparticles were found to promote the formation of PA6 strings with excellent shape stability during shearing. It was ascribed to the promoted coalescence of PA6 droplets induced both by the significantly increased droplet viscoelasticity and confinement, and the reduced interfacial tension by adding silica nanoparticles. Additionally, the width and aspect ratio of droplets obtained by experiments were compared with the predictions of Maffettone–Minale, Minale, Shapira‐Haber, MMSH, and modified M models. Good agreements were found in the droplet width in blends with low nanoparticle concentrations, whereas the experimental aspect ratio showed a negative deviation to model predictions, which was attributed to the enhanced droplet viscoelasticity and the omitted droplet orientation angle in these models. © 2015 American Institute of Chemical Engineers AIChE J, 62: 564–573, 2016